Effect of Nd/Mg co-doping on the electrical properties of ceria-based electrolyte materials. (23rd February 2017) - Xie, Shenkun; Liu, Ying; Xi, Wenguang; Zhou, Defeng; Meng, Jian
Abstract : A series of Nd/Mg co-doped ceria electrolytes, Ce0.8 Nd0.2− x Mg x O2−δ ( x = 0, 0.05, 0.10 and 0.15), were synthesised through a facile solgel method. The structure and electrical properties were characterised by X-ray diffraction, scanning electron microscopy and AC impedance spectroscopy. An appropriate elemental ratio of Nd/Mg in the co-doped experiment was found to be essential in improving the electrical performance of the ceria-based electrolytes. The optimum grain-boundary conductivity (2.28 × 10 −2 S cm −1 ) and total conductivity (2.68 × 10 −3 S cm −1 ) were obtained at the doping 10 at.% Nd and 10 at.% Mg.